2019
DOI: 10.26717/bjstr.2019.15.002647
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation in Radionuclide Therapy Dosimetry

Abstract: Monte Carlo [MC] method is a modeling tool, capable of achieving a close adherence to reality, concerning the analysis of complex systems. Generally is a method for estimation of the solution of mathematical problems by means of random numbers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[17][18][19] Although DPK methods generally offer better speed to calculate dose deposited in a voxelized patient body, they use generic dose kernels simulated in a homogeneous phantom made of a material like soft tissue. 20 For dose calculation in the presence of heterogeneities, the DPK method requires the use of a kernel scaling approach. 21 However, Khan and DeWerd simulated scaled DPKs based on mass density for various tissues and found that corrected DPKs could differ by up to 25% near Bragg peak regions when compared with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Although DPK methods generally offer better speed to calculate dose deposited in a voxelized patient body, they use generic dose kernels simulated in a homogeneous phantom made of a material like soft tissue. 20 For dose calculation in the presence of heterogeneities, the DPK method requires the use of a kernel scaling approach. 21 However, Khan and DeWerd simulated scaled DPKs based on mass density for various tissues and found that corrected DPKs could differ by up to 25% near Bragg peak regions when compared with water.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D matrix of TIAs is then convolved with a pregenerated 3D dose point kernel (DPK) or serves as input for MC code simulations 17–19 . Although DPK methods generally offer better speed to calculate dose deposited in a voxelized patient body, they use generic dose kernels simulated in a homogeneous phantom made of a material like soft tissue 20 . For dose calculation in the presence of heterogeneities, the DPK method requires the use of a kernel scaling approach 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s, based on the sequential importance sampling (SIS) [ 22 , 23 ], Gordon proposed a particle filter (PF) algorithm [ 24 , 25 ] by combining the resampling technique with Monte Carlo importance sampling. This algorithm is an optimal regression algorithm, combining Monte Carlo thought [ 26 ] and recursive Bayesian filtering [ 27 ], and it has a good estimation effect when dealing with nonlinear/non-Gaussian systems [ 28 , 29 , 30 ]. However, particle degradation and particle shortage occur during particle sampling, which seriously affects the accuracy of the PF.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years scientists use simulation methods to overcome such situations. One of the most powerful methods used in radiation calculations is Monte Carlo (MC) simulations, which are commonly used in medical radiation physics (17)(18)(19). This is a theoretical model in which physical quantities are determined by simulating the transport of X-ray photons.…”
Section: Introductionmentioning
confidence: 99%